Mass spectrometry-based SNP genotyping as a potential tool for ancestry inference and human identification in Chinese Han and Uygur populations. Issue 3 (May 2019) - Zhang, Jiashuo; Zhang, Jingyi; Tao, Ruiyang; Yang, Zihao; Zhang, Suhua; Li, Chengtao
Abstract: Ancestry informative SNPs (AISNPs) are genetic variants that exhibit substantially different frequencies between populations from different geographical regions; thus, they can provide some valuable information regarding samples and be used in predicting an individual's ancestry origin. In this study, we selected the potentially best SNPs from our previous study with genome-wide high-density SNP data in mainland Chinese Uygur and Han populations and investigated the allele distribution patterns and genetic information of AISNPs with a mass spectrometry-based SNP genotyping panel. Mass spectrometry-based detection technology offers the opportunity to analyze forensic DNA samples and obtain SNP variants with accuracy and ease. The panel can distinguish and cluster Han and Uygur populations and is suitable for human identification and parentage testing in the two populations. Heatmap, PCA, and Structure analyses indicated that the ideal 64 AISNPs can collectively provide additional information on differences among populations from East Asia, South Asia, Europe and Africa. Additionally, the results proved that the Uygur population is the admixture of East Asia and Europe. Highlights: This work uses an efficient and low-cost technology to obtain SNP variants. The custom SNP panel can distinguish Han and Uygur populations. The custom SNP panel is suitable for human identification and parentage testing. Half of the recommended DNA can be used to obtain reliable genotyping results.